EXPERIMENTAL PETROLOGY AND PETROGENESIS OF MARE VOLCANICS - Longhi J. (My University, 1992)
Mare volcanics consist of basalts and picritic pyroclastic glasses spanning a wide range of TiO2 concentration. The more primitive low-Ti basalts and picritic glasses have olivine alone on their lowpressure liquidi. Most of the chemical variation among the low-Ti basalts is the result of olivine fractionation in a series of parental MgO-rich liquids differing in TiO2 concentration. With one possible exception (Apollo 17 VLT) none of the picritic compositions is a suitable parent for any of the observed low-Ti basalts. Most of the chemical variation among the high-Ti basalts is the result of a series of magmas fractionated along the low-pressure olivine + armalcolite/ilmenite cotectic. All of the picritic high-Ti glasses have olivine alone on the liquidus, but none is a suitable parent for any of the basalts. Volcanics with intermediate TiO2 concentrations (5 to 10 wt%) are widespread in the maria, even though they are not well represented in the sample collections; however, there is no evidence either among the samples or from remote sensing studies of basalts with > 13 wt% TiO2 that would be expected as differentiates of the picritic glasses with the highest TiO2 concentrations.